Identification of α°-thalassaemia (–SEA) using an enzyme-linked immunosorbent assay (ELISA) for embryonic zeta-globin chain detection – a preliminary study - Tan, Mary Anne Jin Ai; George, Elizabeth; Lim, E. J.; Zakaria, Z.; Hassan, R.; Wee, Y. C.; Tan, K. L. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2006)
Objectives: This study aimed to evaluate the UBI MAGIWELTM ζ-GLOBIN ELISA Kit for the presumptive diagnosis of αo-thalassaemia. The ELISA results obtained were confirmed by molecular characterisation of αo-thalassaemia using a Duplex-PCR. Methods: Routine peripheral blood counts and red cell indices were determined in 94 blood samples sent for Hb analysis. Hb subtypes were quantified by high performance liquid chromatography (HPLC) and Hb electrophoresis conducted on agarose gel at pH 8.5. Zeta-globin chain levels were determined using the UBI MAGIWELTM ζ-GLOBIN ELISA Kit. Molecular analysis was performed using a duplex-PCR which simultaneously amplifies a normal 136 bp sequence between the ψα−α2-globin genes and a 730 bp Southeast Asian deletion-specific sequence (–SEA) between the ψα2−θ1-globin genes. Results: Using the ELISA assay kit, 20 blood samples were presumptively identified as α-thalassaemia carriers from elevated ζ-globin chains (OD>0.3) while the remaining 74 blood samples showed OD<0.3. Molecular characterisation confirmed amplification of the 136 bp normal fragment in all the blood samples. Seventeen of the 20 DNA samples from the α-thalassaemia carriers amplified the SEA-deletion specific fragment. The remaining three DNA samples did not amplify the SEA-deletion specific fragment but amplified the normal α-globin gene sequence, indicating the presence of amplifiable DNA in these samples. Further molecular characterisation of the α-3.7 and -α4.2 deletions and Hb Constant Spring (CS) mutation showed the absence of these defects in these 3 DNA samples. Conclusion: This preliminary investigation showed the sensitivity and specificity of the UBI MAGIWEL ζ-globin ELISA kit as 100 % and 96.1 % respectively in the detection of α-thalassaemia-1 carriers (–SEA).